Empowering Employees: Strategic HR Management for Organizational Excellence - Ardyansyah, Farid; Faliza, Nur; Estiana, Ria (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study investigates the relationship between strategic human resource management (SHRM), employee engagement, employee empowerment, and organizational excellence within the context of Hannah Hotel Syariah, a Syariah-compliant hospitality business. Utilizing a quantitative research design, data were collected from 50 employees through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The results reveal that SHRM has a significant positive impact on both employee engagement and organizational excellence, with employee engagement playing a critical mediating role between SHRM and organizational outcomes. However, employee empowerment did not have a direct or indirect effect on organizational excellence in this context. These findings highlight the importance of engagement strategies aligned with organizational and religious values in achieving long-term success. The study concludes that SHRM practices that focus on enhancing employee engagement can improve both employee satisfaction and the overall performance of Syariah-compliant organizations.